2018
DOI: 10.1038/s41593-018-0101-9
|View full text |Cite|
|
Sign up to set email alerts
|

Dysregulation of the epigenetic landscape of normal aging in Alzheimer’s disease

Abstract: Aging is the strongest risk factor for Alzheimer’s disease (AD), although the underlying mechanisms remain unclear. The chromatin state, in particular through the mark H4K16ac, has been implicated in aging and thus may play a pivotal role in age-associated neurodegeneration. Here we compare the genome-wide enrichment of H4K16ac in the lateral temporal lobe of AD individuals against both younger and elderly cognitively normal controls. We found that while normal aging leads to H4K16ac enrichment, AD entails dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
235
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(284 citation statements)
references
References 69 publications
30
235
1
1
Order By: Relevance
“…To test the relevance of this phenomenon for lncRNAs at large and for LINC‐PINT specifically, we measured the expression of LINC‐PINT in AD and HD by investigating brain expression data from WADs of effected individuals and neurologically normal controls. We identified a 45% elevation of LINC‐PINT in the lateral temporal lobe of AD patients compared to healthy donors (Figure h, GSE104704) (Nativio et al, ). LINC‐PINT elevation in AD was also reproduced in our own RNA‐Seq cohort (Barbash, Garfinkel, et al, ), where patients were divided into sub‐groups based on their cognitive impairment and their brain pathology.…”
Section: Resultsmentioning
confidence: 89%
“…To test the relevance of this phenomenon for lncRNAs at large and for LINC‐PINT specifically, we measured the expression of LINC‐PINT in AD and HD by investigating brain expression data from WADs of effected individuals and neurologically normal controls. We identified a 45% elevation of LINC‐PINT in the lateral temporal lobe of AD patients compared to healthy donors (Figure h, GSE104704) (Nativio et al, ). LINC‐PINT elevation in AD was also reproduced in our own RNA‐Seq cohort (Barbash, Garfinkel, et al, ), where patients were divided into sub‐groups based on their cognitive impairment and their brain pathology.…”
Section: Resultsmentioning
confidence: 89%
“…Differential peaking analysis has suggested that there is more peak loss in AD patients [24]. H4K16ac, another aging-related active transcription marks also indicated a tendency of H4K16ac mark loss [23]. Tau protein burden is reported to have a broad effect on the epigenome [19].…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide studies of CpG islands identified altered DNA methylation and suggested their impacts on the AD risk genes [22]. Histone modification studies to active epigenetic marks, such as H4K16ac, H3K9acand H3K27ac, suggested that abnormal epigenetic regulation affects the regulation of AD genes [23,24]. Additionally, recent studies reported that large-scale changes in H3K27ac could be driven by tau pathology in human brains [19] and that HDAC3 inhibition could reverse AD-related pathologies in the animal model of AD [25].…”
mentioning
confidence: 99%
“…Furthermore, recent studies in AD have relied on bulk tissue (16)(17)(18), potentially masking epigenomic changes that occur in rare cell types. For example, microglia constitute around 5% of brain cells, therefore analysis of bulk tissue renders microglia-specific enhancers difficult to detect.…”
Section: Introductionmentioning
confidence: 99%